Nursing and Patient Care in Childhood Cancer: Mini Review - Fatimah Mohammed Alkhazal; Maryam Taher Alkhamis; Nouf Ameen Ahmed Al Hashim; Meryam Mohammed Alabbad; Bashayr Ameer Alshawakir; Areej Saud Alarab; Kulthum Ahmed Al Mahdi; Hussain Ali Jwad Alahmad; Lolowa Yosef Ibrhim Alsrheid; Ammar Fadhel Ahmad Ben Ammar (International Journal of Scientific Research and Innovative Studies, 2022)
Childhood cancer poses unique challenges that require specialized nursing care to ensure optimal outcomes and the well-being of pediatric patients. This comprehensive review article examines the role of nursing in providing patient-centered care for children with cancer. It explores various aspects of nursing care, including symptom management, psychosocial support, family involvement, and long-term survivorship. Additionally, evidence-based practices and interventions that enhance nursing care in childhood cancer are discussed.